A construal of the understanding level of quality assurance by internal stakeholders in two Malaysian universities - Njie, Baboucarr; Asimiran, Soaib (Hipatia Press, 2016)
The “understanding” in terms of interpretation of quality assurance is essential for the acceptance, theorizing and the practical application of the methods proposed by it. A great deal of research papers have often pointed to the lack of understanding, among others, as the reason behind the inadequate nature of implementing quality assurance in higher education institutes. This paper examines the “understanding” levels of two key stakeholders in terms of the meaning they make out of the policy pronouncements on quality. It utilizes the qualitative case study scheme to provoke the thoughts of mainly the academic staff and their administrative counterparts in two public universities. The findings reveal that there exist differences which are mainly grounded on their role and experience in the scope of understanding the purposes served by quality, and the depths of quality management fulfillment among the two categories of stakeholders. This underpins the value of clarifying the philosophy of quality assurance to stakeholders and their involvement for better understanding and ownership.